(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
In recent years, polypropylene (PP) has been tremendously explored in high voltage cable applications due to its outstanding thermal and electrical properties. Furthermore, PP is an environment-friendly material that can be recycled, thus making it a promising candidate to replace conventional crosslinked polyethylene. However, the stiffness and brittleness of PP need to be further modified so that it can be utilized for practical cable applications. Recently, elastomer blending has been one of the favorable methods used by the industry to modify PP flexibility. Unfortunately, different types of elastomers bring different compatibility in the PP matrix. In this paper, the dielectric performance of PP, when mixed with ethylene-butene elastomer (EBE), was investigated. The thermal behaviors and morphological analysis were identified by using a differential scanning calorimeter and scanning electron microscopy, respectively. Meanwhile, the direct current (DC) breakdown strength was set up referring to the ASTM D3755 standard. Based on the findings, EBE shows a certain degree of compatibility with PP, where uniformly distributed spots were observed. Although the addition of EBE slightly degraded the DC breakdown properties of PP, the performance of PP/EBE blends at low elastomer contents is still good enough compared to conventional XLPE.